2015
DOI: 10.1111/bju.13002
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of erectile function after transrectal ultrasonography‐guided prostate biopsy

Abstract: ObjectiveTo prospectively evaluate the effect of transrectal ultrasonography (TRUS)-guided prostate biopsy on erectile and voiding function at multiple time-points after biopsy. Patients and MethodsAll men who underwent TRUS-guided prostate biopsy completed a five-item version of the International Index of Erectile Function (IIEF-5) and the International Prostate Symptom Score (IPSS) before and at 1, 4 and 12 weeks after TRUS-guided biopsy. Statistical analyses used were a general descriptive analysis, continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 17 publications
3
28
1
4
Order By: Relevance
“…Several studies have investigated the effect of TP or TRUS biopsies on erectile function and the relationship of prostate biopsies and associated anxiety, with the conclusion that prostate biopsies cause anxiety and temporary erectile dysfunction,27 which may be worse after multiple biopsy episodes 162829. Finally, we did not account for co-morbidity, but given this is a relatively young patient cohort, suitable for treatment with curative intent, we would expect these not to be a significant confounder.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of TP or TRUS biopsies on erectile function and the relationship of prostate biopsies and associated anxiety, with the conclusion that prostate biopsies cause anxiety and temporary erectile dysfunction,27 which may be worse after multiple biopsy episodes 162829. Finally, we did not account for co-morbidity, but given this is a relatively young patient cohort, suitable for treatment with curative intent, we would expect these not to be a significant confounder.…”
Section: Discussionmentioning
confidence: 99%
“…Murray et al showed 34% of patients with no ED at baseline had a decrease in IIEF score at 1 week; 20% and 24% continued to have lower scores at 1 and 3 months, respectively. Age ≥60 years or above, the first biopsy setting and a diagnosis of PCa were the main predictors of IIEF score impairment at 1 and 3 months 31 . It has been hypothesized that extensive sampling during saturation PB could affect erectile function, but in multiple series the IIEF score impairment resolved within 6 months after biopsy, and no correlation was found between number of cores and IIEF scores 28,32 .…”
Section: Erectile Dysfunctionmentioning
confidence: 97%
“…Transrektal USG eşliğinde yapılan prostat biopsiden sonra belirli oranlarda hematüri, Prostat biopsisinden sonra ED oranını saptamak için yapılan çalışmalarda istatistiksel anlamlı artış olmadığını söyleyen çalışmalar olsa da son zamanlarda bu durumun aksini söyleyen birçok yayınlanmış makale bulunmaktadır (6)(7)(8). Erektil disfonksiyon prostat biopsisinden sonra erken zamanlarda görülüp sıklıkla zamanla iyileşmektedir (9).…”
Section: Discussionunclassified
“…Erektil disfonksiyon prostat biopsisinden sonra erken zamanlarda görülüp sıklıkla zamanla iyileşmektedir (9). Periprostatik sinir bloğunun nörovasküler demette yarattığı hematom, ödem nedeniyle daha fazla erektil fonksiyon kaybı yarattığı görüşü diğer prospektif çalışmalarla desteklenmemiştir (4,8,9). Diğer bir çalışma ağrı skorunun daha az olmasının erektil fonksiyondaki değişime etkisi olmadığını yayınlamıştır (10).…”
Section: Discussionunclassified
See 1 more Smart Citation